Is tuberculosis patients management improved in the integrated TB control model in West China? A survey in Guizhou Province, China - Jie Pu; Wei Chen; Wei-Xi Jiang; Wei Xing; Sheng-Xiang Liang; Geng Wang; Shi-Li Liu; Hao Wu; Ying Li; Sheng-Lan Tang (BMC, 2019)
Abstract Background Tuberculosis (TB) patient management (TPM) is crucial to improve patient compliance to treatment. The coverage of TPM delivered by TB dispensaries or Centers for Disease Control and Prevention (CDC) was not high under the previous CDC model of TB control in China. In the integrated TB control model in China, TB patient management (TPM) was mainly delivered by lay health workers (LHWs) in primary health care (PHC) sectors. This study aims to investigate TPM delivery in resource-limited western China and to identify factors affecting TPM delivery by LHWs under the integrated TB control model. Methods A stratified random sampling was used to select study sites. Pulmonary TB (PTB) patients ≥15 years old from selected counties/districts in Guizhou Province were surveyed from August 2015 to May 2016. Structured questionnaires were used to collect data. A χ 2 test and logistic regression were used to identify factors associated with self-administered treatment (non-TPM). Results In total, 638 PTB patients were included in the final analysis. Close to 30% of patients were ethnic minorities. More than 30% of patients were from counties with high TB burden, and 24.9% of patients had poor compliance to treatment. Only 37.1% of patients received TPM delivered by LHWs under the integrated TB control model throughout the treatment period. The main reasons for unwillingness to manage reported by patients included social stigma and no perceived need. Being ethnic minorities (OR = 3.35) was a main factor associated with lower likelihood of receiving TPM, while living in areas with middle or high TB burden may increase the likelihood of receiving TPM (OR = 0.17 and 0.25, respectively). Among current management approaches, more than 85% of patients chose phone reminder as their preferred TPM by LHWs. Conclusions TPM under the integrated model in West China is still low and need further improvement, and the impeding factors of TPM need to be addressed. Strengthening patient-centered and community-based TPM and developing more feasible approaches of TPM delivery should be explored in future research in this region.